Experimental Study on Flexural Behavior of Prestressed Concrete Beams Reinforced by CFRP under Chloride Environment - Yunyan Liu; Yingfang Fan (Advances in Civil Engineering)
In order to study the effects of initial damages, CFRP reinforcement, and chloride corrosion on the flexural behavior of prestressed concrete beams, ten prestressed concrete beams were designed and manufactured, which were preloaded with 0%, 40%, and 60% of the ultimate load to crack. Then, part of the beams were reinforced by CFRP and immersed in chloride condition for 120 days. After that, the four-point bending tests were performed. Then, the sectional strain, deformation, flexural stiffness, flexural capacity, ductility, and the cracking characteristics were researched. The test results demonstrate that the sectional strain of PC beams still follows the plane cross section assumption after a pure bending deformation considering of the initial cracks, chloride corrosion, and CFRP reinforcement. The initial damage accelerates the chloride corrosion, resulting in the loss of initial stiffness, ductility, and cracking load, and the reduction in flexural capacity is less than 10%, and the failure modes of these beams are prone to change from concrete crushing to shear failure. In the cracking stage, the reinforcement of CFRP inhibits the bending deformation, leading to the reduction in stiffness degradation rates and the increase of cracking load, and the ultimate load increases by 12.8%∼18.7%. The reinforcement of CFRP constrains the development of cracks, increases the cracks numbers by 50%∼130%, decreases the cracking rates of beam bottoms by 52.5%, and reduces the average crack widths by 65.8% at 195 kN. It can be seen that the reinforcing effect of CFRP is more significant compared with the weakening effect of short-term chloride corrosion and initial damage on the flexural behavior.